Optimalisasi Proses Administrasi Dan Pengelolaan Fasilitas Serta Permintaan Barang PT XYZ Dengan Metode WBS (Work Breakdown Structure) - Muhammad Sandi Kurniawan; Joumil Aidil SZS (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Administrative process optimization is a systematic effort to improve efficiency, productivity, and quality in the execution of administrative tasks within the company, while facilities management and demand for goods and logistics focus on improving operational efficiency and effectiveness, which will apply the WBS method to decompose complex tasks into more manageable components. This analysis is expected to increase visibility, engagement, and understanding of each stage in the administrative, facilities management, and logistics management processes, enabling more targeted and impactful change implementation. Overall, this research is geared towards achieving improved performance and efficiency at PT XYZ through the application of WBS methodology in the context of the company's administration and logistics.